Why do migrants remit?: an analysis for the Dominican Sierra - de la Briere, Benedicte; de Janvry, Alain; Lambert, Sylvie; Sadoulet, Elisabeth (International Food Policy Research Institute, 1997)
Two contrasting hypotheses about what motivates Dominican migrants to send remittances to their rural parents in the Sierra are tested: (1) an investment in potential bequests and (2) an insurance contract between parents and migrant children. Remittances from young migrants, males, and migrants who want to return to the Sierra follow a pattern consistent with investment. In contrast, female migrants with no intention of returning to the Sierra play the role of insurers. The gender composition of the migrant siblings affects this remittance task-sharing, since women with no remitting brothers show interest in inheritance, while men with no sisters offer insurance.